Institutional concepts - Redondo, María Cristina (Revus (Ljubljana), 2020)
This paper proposes a reflection on specific kinds of legal concepts: those that delimit and allow us to identify legal institutions. In the first part, three proposals that are presented as competitive visions of these kinds of institutional concepts are taken into account: First is Ronald Dworkin's interpretative-justifying conception; second is the reductionist conception associated with the realistic theory of Alf Ross; finally, the criterial conception supported by a normative legal positivism. In the second part of the work, these three proposals are applied to a specific legal institution: the crime of witchcraft. The paper has two fundamental objectives: On the one hand, to show that the analytical and metatheoretical approach of normative legal positivism is not reducible to any of the other two and, in turn, relevant from a practical point of view. On the other hand, to show that the presentation of the considered proposals as if they were competing approaches to institutional concepts is misleading. They don't talk about the same thing. They are guided by different methodological objectives and, above all, answer different questions concerning legal institutions.
Keywords: criterial concepts; čarovništvo; false beliefs; institucije; institucionalni pojmi; institutional concepts; institutions; interpretative concepts; interpretativni pojmi; kriterijski pojmi; witchcraft; zmotna prepričanja